Kewenangan Mengadili Lembaga Peradilan di Indonesia Dan Titik Singgung Pengadilan Umum Dengan Pengadilan Agama - Halimi, Moh. Zunaidi (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
The court as an officially legitimate (legitimate) state institution is given the authority to examine, adjudicate, decide and resolve every dispute submitted to it. The Court's authority, practical and theoretical, is divided into two, namely absolute authority (absolute competency) and relative authority (relative competency, jurisdiction). The method used is literature review, which is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and ideas that have been produced by researchers and practitioners. The type of research that researchers used in preparing this article is research. Qualitative, this kind of research is descriptive and tends to use analysis with an inductive approach. This type of qualitative research is in the form of library research. As far as current practical experience is concerned, the authority of district courts and religious courts often experiences points of contact. Apart from historical factors, incomplete factors and lack of clear explanations in the law give rise to different interpretations regarding the authorities in certain cases. Moreover, the absolute authority of religious courts is based on the principle of Islamic personality, which means that submission to the provisions of Islamic law is the basis for the legitimacy of the authority of religious courts in certain cases. Submission to Islamic provisions as the basis for the meaning of Islamic personality no longer only means formal Muslims (based on legal identity), but also non-Muslims who submit themselves to the provisions of Islamic law. Below are several points regarding the authority of the District Court and the Religious Court.